A novel methodology to characterize beat-to-beat alternations in whole-cell calcium currents - Xavier Marimon; Miguel Cerrolaza; Carmen Tarifa; Leif Hove-Madsen (PLoS ONE, 2026)
An automated high-throughput procedure to quantify the degree of electrical beat-to-beat alternants in human atrial myocytes from electrophysiological recordings of the transmembrane ion currents of calcium ions ( Ca 2+ ) is presented and discussed. The patch clamp technique in whole-cell mode was used to record the myocyte calcium signal. A database consisting of 24 patch clamp signals ( N = 24) of which 13 had a uniform behaviour and 11 had an alternating behaviour, was created. Several features were computed to characterize the transmembrane ion currents: peak amplitude, time constants, and area under the ion current trace. The presented algorithm includes a feature detector whose accuracy has been validated using simulated calcium signals generated by an electrical model that accurately represents the cardiomyocyte behaviour in a patch clamp experiment. Among these calculated features, a new index measure, called the “alternation index”, is proposed in this work to quantify the degree of electrical beat-to-beat alternants. The index has been shown to be a robust measure ( p ≤ 0.01 **) for cell detection with an alternating pattern. Good agreement was observed with alternations in other calculated features like the measurement of the inactivation of L-type calcium current ( I ca ) or the tail current ( I Tail ) generated by calcium extrusion upon repolarization.